Ionic Liquid [Bmim]PF6 Plasticize Polylactic Acid - Wang, Zhoufeng; Chen, Peng; Chen, Zhichong; Yu, Zhixiang (Asian Journal of Chemistry, 2014)
Room temperature ionic liquid 1-butyl-3-methylimidazolium hexafluorophosphate ([Bmim]PF6) was studied as novel plasticizers for polylactic acid. The mixture process was carried out in molten state. [Bmim]PF6 were found to be excellent plasticizers for polylactic acid, with improved thermal stablity and plasticity. The microstructure indicated that novel plasticizer make agglomeration of CaCO3 particles and phase separation easy, which might be due to the reduction of melt viscosity and the [Bmim]PF6 concentration on the CaCO3 particles.